Microbiome or Infections: Amyloid-Containing Biofilms as a Trigger for Complex Human Diseases - Miller, Amanda L.; Bessho, Shingo; Grando, Kaitlyn; Tükel, Çagla (Frontiers in Immunology, 2021)
The human microbiota is the community of microorganisms that live upon or within their human host. The microbiota consists of various microorganisms including bacteria, fungi, viruses, and archaea; the gut microbiota is comprised mostly of bacteria. Many bacterial species within the gut microbiome grow as biofilms, which are multicellular communities embedded in an extracellular matrix. Studies have shown that the relative abundances of bacterial species, and therefore biofilms and bacterial byproducts, change during progression of a variety of human diseases including gastrointestinal diseases, autoimmune diseases, neurodegenerative diseases, cardiovascular diseases, and cancer. Recent studies suggest the physical location or proximity of the biofilms within the gastrointestinal tract might impact disease outcome. Gram-negative enteric bacteria secrete the amyloid curli, which makes up as much as 85% of the extracellular matrix of enteric biofilms. Curli mediates cell-cell attachment and attachment to various surfaces including extracellular matrix components such as fibronectin and laminin. Structurally, curli is strikingly similar to pathological and immunomodulatory human amyloids such as amyloid-β, which has been implicated in Alzheimer’s disease, α-synuclein, which is involved in Parkinson’s disease, and serum amyloid A, which is secreted during the acute phase of inflammation. The immune system recognizes both bacterial amyloid curli and human amyloids utilizing the same receptors, so curli also induces inflammation. Moreover, recent work indicates that curli can participate in the self-assembly process of pathological human amyloids. Curli is found within biofilms of commensal enteric bacteria as well as invasive pathogens; therefore, evidence suggests that curli contributes to complex human diseases. In this review, we summarize the recent findings on how bacterial biofilms containing curli participate in the pathological and immunological processes in gastrointestinal diseases, systemic autoimmune diseases, and neurodegenerative diseases.